Distribution pattern of hepatitis c virus in eastern peninsular malaysia for the past decade - H.M, Hadzr; Tee, Hoi Poh; Che Aun, Azlida (The Faculty of Medicine, International Islamic University Malaysia, 2015)
Introduction: Analysis of the Hepatitis C Virus’ (HCV) genotypic spread in a particular area has a crucial impact on public health. Genotyping is essential before initiating treatment. Methodology: This is a hospital-based cohort of 133 chronic hepatitis C patients, collected prospectively among subjects attending Hospital Tengku Ampuan Afzan, Kuantan, within an area of eastern Peninsular Malaysia. We assessed the rate and distribution of HCV genotypes during two consecutive periods, from 2005 to 2006 and from 2013 to 2014, according to age, gender, race and risk factors.